EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL, DAN KUALITAS LAPORAN KEUANGAN DAERAH - Ika Prayanthi; Prilisita Olivia Salangka (UNKLAB Business School, 2020)
This study aims to obtain information related to the application of accounting information systems, internal control systems and the quality of financial reports in the Regional Government of Manado City. The method used in this research is descriptive method. Respondents who filled out the questionnaire were divided into two groups, namely the finance department employees to answer questions related to the application of accounting information systems and internal control systems, and the other group was the finance inspectorate who answered questions related to the quality of financial statements. The number of respondents for the first group was 40 employees in the finance department, while for the second group, the inspectorate was 25 people. The results of the study found that more than 50 percent of employees in the finance department agreed to state that the effective accounting information system and internal control system had been implemented in accordance with existing procedures. Likewise with the variables related to the quality of financial statements, it was found that more than 50% of the inspectorates agreed that the financial reports produced by the Regional Government of Manado City were already qualified. The results of the study can be the basis for the Regional Government of Manado City to maintain and even improve performance in processing finance and administration in presenting financial statements. Keywords: Accounting information system, internal control system, quality of financial statement Penelitian ini bertujuan untuk mendapatkan informasi terkait penerapan sistem informasi akuntansi, sistem pengendalian internal serta kualitas laporan keuangan di Pemerintah Daerah Kota Manado. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Responden yang mengisi kuesioner ini dibagi menjadi dua kelompok yakni karyawan bagian keuangan untuk menjawab pertanyaan terkait penerapan sistem informasi akuntansi dan sistem pengendalian internal, serta kelompok yang lainnya adalah inspektorat bagian keuangan yang menjawab pertanyaan terkait kualitas laporan keuangan. Adapun jumlah responden untuk kelompok pertama yakni karyawan bagian keuangan berjumlah 40 orang sedangkan untuk kelompok kedua yakni inspektorat adalah sejumlah 25 orang. Hasil penelitian mendapati bahwa lebih dari 50 persen karyawan bagian keuangan setuju menyatakan bahwa telah diterapkannya secara efektif sistem informasi akuntansi dan juga sistem pengendalian internal telah diterapkan sesuai dengan prosedur yang ada. Demikian juga dengan variabel terkait kualitas laporan keuangan, didapati bahwa lebih dari 50% para inspektorat setuju bahwa laporan keuangan yang dihasilkan oleh Pemerintah Daerah Kota Manado adalah sudah berkualitas. Hasil penelitian dapat menjadi basis agar Pemerintah Daerah Kota Manado mempertahankan bahkan meningkatkan kinerja dalam mengolah keuangan serta administrasi dalam menyajikan laporan keuangan. Kata kunci: Kualitas laporan keuangan, sistem informasi akuntansi, sistem pengendalian internal